2018
DOI: 10.1016/j.jval.2018.09.2289
|View full text |Cite
|
Sign up to set email alerts
|

Prm170 - Utilizing Patient Collages in Qualitative Interviews to Facilitate Data Collection in Patients Diagnosed With Ulcerative Colitis

Abstract: OBJECTIVES: Cost-utility analyses need a measure to summarize the quality of life in a single index. A single score is often obtained by the EQ-5D questionnaire which is adaptable to each country with score tariffs. In clinical studies it is common to use questionnaires that measure the quality of life profile, such as the SF-36 psychometric questionnaire and then realized the mapping technique to obtain this utility score. Today no specific regression method has been recommended for a such mapping. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Another creative task used in this study involved asking participants to think about an animal which might represent their UC, and to explain their choice of animal. The value of creative tasks (such as collages and the animal task) to qualitative research has been shown to be particularly useful when interviewing younger participants in order to prompt discussion and orientate the participant to think about key areas of concern relating to their disease ahead of the interview [28]. Given the potential benefits of such a task, it was agreed to extend both tasks to adults as well as adolescent participants.…”
Section: Methodsmentioning
confidence: 99%
“…Another creative task used in this study involved asking participants to think about an animal which might represent their UC, and to explain their choice of animal. The value of creative tasks (such as collages and the animal task) to qualitative research has been shown to be particularly useful when interviewing younger participants in order to prompt discussion and orientate the participant to think about key areas of concern relating to their disease ahead of the interview [28]. Given the potential benefits of such a task, it was agreed to extend both tasks to adults as well as adolescent participants.…”
Section: Methodsmentioning
confidence: 99%
“…All children were asked to develop and bring to their interview a collage representing their UC, though this was a voluntary activity and not required. If a collage was brought, the interviewer asked the participant to explain what each image represented, which allowed this information to facilitate coding [28]. A second creative task involved asking all child participants to think of an animal best representing their UC and probing their choice.…”
Section: Interviewsmentioning
confidence: 99%
“…This was included to identify which aspect/s of their UC the child may see as most salient and allow further exploration of it in the interview. The value of such creative tasks to qualitative research has been shown to be particularly marked when interviewing younger participants in order to prompt discussion and orient the participant to think about key areas of concern relating to their disease ahead of the interview [28].…”
Section: Interviewsmentioning
confidence: 99%